EFFECT OF TIME AND TEMPERATURE OF RETROGRESSION AND REAGING HEAT TREATMENT ON MECHANICAL PROPERTIES AND STRESS CORROSION CRACKING BEHAVIOR OF ALUMINIUM ALLOY 7075 - Fudin Husni, Syaro
Aluminum alloy 7075 is one type of high-strength aluminum alloy with a specific strength of around 120-250 MPa/(kg/m³), which is often used in aircraft frames. However, under T651 usage conditions, where its mechanical properties are optimal, this alloy is susceptible to failure due to stress corrosion cracking (SCC). SCC occurs due to the dissolution of precipitates at grain boundaries when the aircraft operates in an environment close to seawater. In aging heat treatment, the SCC resistance is inversely proportional to the strength of the alloy. Therefore, retrogression and reaging (RRA) treatment was developed to improve SCC resistance without reducing the strength of the alloy. This study analyzes the effect of RRA heat treatment to obtain an optimal combination of mechanical properties and SCC resistance. A series of heat treatment experiments have been conducted to analyze the effect of retrogression time and temperature on mechanical properties and SCC resistance. The heat treatment of T651 was carried out by solution treatment at 480 °C for one hour and precipitation treatment at 120 °C for 24 hours. Furthermore, variations of retrogression heat treatment were carried out at 160 °C, 180 °C, and 200 °C for 10, 20, and 30 minutes, and reaging at 120 °C for 24 hours. Then, characterization was carried out through vickers hardness testing, tensile testing, metallography with an optical microscope, and SEM-EDS analysis. SCC testing was carried out using the constant load test in 5% NaCl solution, with a loading of 300 MPa for seven days to determine the increase in length. Based on the characterization data that had been carried out, the optimum parameters for RRA heat treatment were determined. The results showed that the hardness and strength results were inversely proportional to the increasing time and temperature of retrogression. The highest strength and hardness were obtained at retrogression at 180 °C for 10 minutes, with results of 203.4 HV and 549 MPa, respectively. As the retrogression time and temperature increase, SCC resistance also increases, with the highest resistance achieved in retrogression at 180 °C for 30 minutes, which results in an increase in length of 0.124 mm after testing for seven days. The best combination of strength and SCC resistance was obtained in retrogression at 200 °C for 10 minutes, with a strength value of 543 MPa and an increase in length after seven days of testing of 0.162 mm.